Learning and savings groups in Bangladesh: an alternative model for transforming families and communities. Issue 1 (2nd January 2020) - Marsden, John; Marsden, Kate; Rahman, Mizanur; Danz, Tim; Danz, Andrea; Wilson, Paul
ABSTRACT: Development programmes centred on microfinance have experienced varied levels of success, especially in Bangladesh. Although impact assessments of these development interventions conclude that poor participants' access to credit is enhanced, the same empirical analysis reveals less encouraging results on women's empowerment and community transformation. Food for the Hungry's Family and Community Transformation (FCT) programme represents an alternative model to the traditional microcredit approach to development by emphasising internal savings, holistic training, and the build-up of community-wide social capital. Group graduation to sustainable independence takes a joint commitment of up to ten years.